Implications for Using Digital Twins to Enhance Safety in Warehouse 4.0 Design - Jing Wu; Junru Ren; Ole Ravn; Lazaros Nalpantidis (Chemical Engineering Transactions)
Warehouse 4.0 is the digital transformation of traditional warehouse operations by integrating advanced technologies and automation systems. Digital twin (DT) technology is one of the technologies that can be leveraged to enhance safety in warehouse 4.0 design. This paper addresses three research questions: 1. How do these DT technologies affect safety authorities in assessing the quality of designs? 2. How can DT technologies facilitate early consideration of warehouse 4.0 design in the system lifecycle? 3. What are the implications of using DT technologies for risk assessment and the development of safety cases in human-robot collaboration scenarios?By addressing these research questions, this paper aims to provide a deeper understanding of the role of DT technologies in designing safer intelligent warehouses for the future. Through the integration of DT simulations, early design considerations, and comprehensive risk assessments, stakeholders can leverage DT technologies to proactively enhance safety within Warehouse 4.0 environments, fostering a culture of safety and innovation in the logistics and supply chain industry. Keywords: Artificial intelligence, Digital twin, Loss prevention, Design for Safety, Warehouse 4.0.